Content and Language Integrated Learning (CLIL): Considerations in the Colombian Context (GIST – Education and Learning Research Journal, 2012)
The present article seeks to encourage reflection on the characteristics and considerations when implementing Content and Language Integrated Learning (CLIL) in a diverse context such as the Colombian one. Initially, the general aspects of an innovative and changing education in a globalized world are presented by stating the need to innovate. Secondly, Content and Language Integrated Learning is defined along its implications by critically addressing CLIL dimensions.  Lastly, the article offers a broad view about the inclusion of CLIL in the Colombian context. In general, the article presents the implications about the use of CLIL, specifically its dimensions and influence in Colombia.
Keywords: CLIL; Content Based Instruction; CLIL dimensions